2015
DOI: 10.2478/raon-2014-0031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of whole-body magnetic resonance imaging in health screening of general adult population

Abstract: BackgroundWhole-body magnetic resonance imaging (WB-MRI) and angiography (WB-MRA) has become increasingly popular in population-based research. We evaluated retrospectively the frequency of potentially relevant incidental findings throughout the body.Materials and methods22 highly health-conscious managers (18 men, mean age 47±9 years) underwent WB-MRI and WB-MRA between March 2012 and September 2013 on a Discovery MR750w wide bore 3 Tesla device (GE Healthcare) using T1 weighted, short tau inversion recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 23 publications
0
44
0
Order By: Relevance
“…After reviewing the full text, five studies were excluded because data were also used in another article from the same group, comprising a larger number of patients; one study was excluded because it only reported study rationale and design, and one study was excluded because it was not clear whether the head and neck region was included in the FOV . Eventually, 12 studies were included in this systematic review, published between 2005 and 2018 . Screening the reference lists of these articles did not result in other potentially relevant studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After reviewing the full text, five studies were excluded because data were also used in another article from the same group, comprising a larger number of patients; one study was excluded because it only reported study rationale and design, and one study was excluded because it was not clear whether the head and neck region was included in the FOV . Eventually, 12 studies were included in this systematic review, published between 2005 and 2018 . Screening the reference lists of these articles did not result in other potentially relevant studies.…”
Section: Resultsmentioning
confidence: 99%
“…Tarnoki et al 19 Retrospective Not specified Yes A resident in radiology (2-4 years' experience) and two senior radiologists. Independent reading, discrepancies were resolved in consensus.…”
Section: Prospectivementioning
confidence: 99%
See 2 more Smart Citations
“…6 A further smaller study of 22 healthy volunteers found 20 incidental findings in 20 participants, including a final diagnosis of malignancy in one participant. 7 A study of WB DW-MRI in patients with neurofibromatosis found incidental findings in 104 of 247 (42%) patients, with significant findings in 16 of 247 (6.5%). 8 Our study confirmed that incidental findings are common in WB DW-MRI examinations; however, as DW-MRI is helpful in tissue characterization, only a minority of scans (3%) resulted in equivocal incidental findings requiring further characterization, which limits the impact on patients and resources.…”
mentioning
confidence: 99%